Analysis of the proximal orifice flowfield under pulsatile flow conditions and confining wall geometry: implications in valvular regurgitation - Fan, Pohoey; Perry, Gilbert J.; Anayiotos, Andreas (My University, 1998)
Hemodynamic studies of regurgitant lesions in the heart focus on identifying a reliable noninvasive method of volumetric flow calculation. In these studies the influence of blood viscosity to the flowfield under pulsatile flow conditions and constraining wall geometry has not been examined in detail. Pulsatile flow studies in straight tubes have shown that viscous effects significantly influence the periodic flowfield, especially near the wall. The purpose of this study is to investigate the significance of transient effects in the flowfield proximal to a lesion under constraining wall geometry. The proximal flowfield was analyzed with computational fluid dynamics (CFD) computer simulations and color flow Doppler mapping (CFM). Three different stroke volumes and regurgitant waveforms were investigated for upstream wall orientations that varied from - 64°to + 64°(measured from the orifice plane). Results showed that for each upstream wall orientation, a single instantaneously normalized centerline velocity distribution characterized the flowfield throughout the cycle. The centerline distributions were in phase with the pressure gradient and almost identical to the corresponding steady-state distributions. Minor deviations were observed near the wall, where viscous effects were predominant. Transient flow effects such as blunt profiles and pressure velocity phase shifts, which were observed in straight circular tubes, were not observed in regurgitant orifice flowfields. This is true even under severe confinement conditions.
Keywords: Hemodynamics; Computer simulation; Blood flow